1981
DOI: 10.1111/j.1744-7348.1981.tb04802.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of water shortage on the yield of winter wheat

Abstract: S U M M A R YThe effects of water shortage on the yield of winter wheat (cv. Maris Huntsman) were investigated in covered field plots on silt-loam soil. Plants were subjected to drought at different stages of growth, but none of the treatments significantly decreased yield. Some treatments decreased the number of ears per unit area, and number of grains per ear, but these effects were offset by increases in individual grain weight.We estimate that the soil water deficit (15 1 mm) in the treatment which had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

1982
1982
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 9 publications
3
2
0
Order By: Relevance
“…Results showed that flowering and maturity times were decreased in MWDS and SWDS irrigation regimes. In agreement with our results, Gales and Wilson [ 43 ] with studies in winter wheat, Bannayan et al [ 20 ] in isabgol and black cumin and Alinian and Razmjoo [ 23 ] in cumin ( Cuminum Cyminum L.) reported that water-deficit stress induced a reduction in the time to maturity. This effect is influenced by various factors including the level and duration of the stress, the genotype and the maturity time under non-stress conditions.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Results showed that flowering and maturity times were decreased in MWDS and SWDS irrigation regimes. In agreement with our results, Gales and Wilson [ 43 ] with studies in winter wheat, Bannayan et al [ 20 ] in isabgol and black cumin and Alinian and Razmjoo [ 23 ] in cumin ( Cuminum Cyminum L.) reported that water-deficit stress induced a reduction in the time to maturity. This effect is influenced by various factors including the level and duration of the stress, the genotype and the maturity time under non-stress conditions.…”
Section: Discussionsupporting
confidence: 93%
“…This effect is influenced by various factors including the level and duration of the stress, the genotype and the maturity time under non-stress conditions. Reduced time to maturity is known as a water-deficit stress avoidance mechanism in plants [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…100 mm (Mc-Gowan & Williams, 1980) but matched those for perennial grass swards (Garwood & Sinclair, 1979). The maximum of 186 ±7-6 mm recorded in 1982 represents about 86 % of the water available in the effective rooting zone and is similar to that measured by Gales & Wilson (1981) on a silt loam soil and which in their experiment had no significant effect on yield. The combine grain yield for 1982 in the current experiment when the third wheat crop was grown was only 12% less than that for 1980 (first wheat crop) when the comparable deficit was just 128+ 3 mm.…”
Section: Discussionsupporting
confidence: 60%
“…The combine grain yield for 1982 in the current experiment when the third wheat crop was grown was only 12% less than that for 1980 (first wheat crop) when the comparable deficit was just 128+ 3 mm. The conclusion that in a silt loam, yield would be decreased only by soil water deficits exceeding 180 mm (Gales & Wilson, 1981) appears also to be true for our clay soil.…”
Section: Discussionsupporting
confidence: 56%
“…Soil bulk density and saturated hydraulic conductivity were measured in conjunction with the identification of a compacted layer (pan). In 1980 leaf water potential was measured on two occasions using a leaf pressure ' bomb' as described by Gales & Wilson (1981).…”
Section: Soil Water Regimementioning
confidence: 99%